2015
DOI: 10.1016/j.jacc.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Drug Development

Abstract: Despite the global burden of cardiovascular disease, investment in cardiovascular drug development has stagnated over the past 2 decades, with relative underinvestment compared with other therapeutic areas. The reasons for this trend are multifactorial, but of primary concern is the high cost of conducting cardiovascular outcome trials in the current regulatory environment that demands a direct assessment of risks and benefits, using clinically-evident cardiovascular endpoints. To work toward consensus on impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
84
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 172 publications
(89 citation statements)
references
References 81 publications
2
84
0
3
Order By: Relevance
“…1 In conjunction with an overall ≈90% failure rate of drugs, 2 which impacts directly the rising cost of drug development, this is creating a perfect storm that is threatening to make the development of new drug therapies for CHD prohibitive (estimated currently at $2.6 billion/drug). 3 One potential solution is to use therapeutic targets that have support from genetic studies, such as Mendelian randomization (MR; Figure 1), which is estimated to double the probability that a drug target will succeed in phase III clinical trials.…”
mentioning
confidence: 99%
“…1 In conjunction with an overall ≈90% failure rate of drugs, 2 which impacts directly the rising cost of drug development, this is creating a perfect storm that is threatening to make the development of new drug therapies for CHD prohibitive (estimated currently at $2.6 billion/drug). 3 One potential solution is to use therapeutic targets that have support from genetic studies, such as Mendelian randomization (MR; Figure 1), which is estimated to double the probability that a drug target will succeed in phase III clinical trials.…”
mentioning
confidence: 99%
“…While contemporary trials seem to be becoming more complex, and costly, the emergence of EHR and registry data offer the possibility of novel PCT designs whose form and function are much more similar to the streamlined clinical trials of the 1970s and 80s 31, 32 . The key characteristics of PCTs have been previously reviewed 33, 34 .…”
Section: Pct Background Study Characteristics and Limitationsmentioning
confidence: 99%
“…1 Nevertheless, the development of new drugs for chronic heart failure has waned during the past 20 years; the quantity of novel agents in clinical testing and the number of welldesigned clinical trials have diminished to a small fraction of that seen in the 1980s and 1990s. 2 Some have suggested that investment in heart failure has declined because the primary mechanisms of the disorder are poorly understood, because the promising results of phase II trials are frequently not confirmed in large-scale definitive studies, and because the large-scale clinical trials needed for regulatory approval have often become prohibitively expensive. 2,3 We know that clinical research in heart failure is extremely challenging, and so we beg innovators in the pharmaceutical and device industries to be patient, and we plead with sponsors to invest in large-scale investigations because the need is so great.…”
mentioning
confidence: 99%
“…2 Some have suggested that investment in heart failure has declined because the primary mechanisms of the disorder are poorly understood, because the promising results of phase II trials are frequently not confirmed in large-scale definitive studies, and because the large-scale clinical trials needed for regulatory approval have often become prohibitively expensive. 2,3 We know that clinical research in heart failure is extremely challenging, and so we beg innovators in the pharmaceutical and device industries to be patient, and we plead with sponsors to invest in large-scale investigations because the need is so great. Yet, when we critically examine how we react to data, it may not be too surprising that meaningful clinical trials in heart failure are becoming increasingly scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation